The Effects of Papain Enzyme Supplement in Feed on Protein Digestibility, Growth and Survival Rate in Sangkuriang Catfish (Clarias sp) - Diana Rachmawati; Istiyanto Samidjan (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
The study aimed to assess the effects of Papain Enzyme Supplement in Feed on Protein Digestibity, Growth and Survival Rate of Sangkuriang Catfish (Clarias sp). Fingerlings used in the study were acquired from the Center for Freshwater Hatchery and Aquaculture, Muntilan, Central Java, Indonesia. The fingerlings had average weight of 3.43±0.50 g/fish. Completely Randomized Design was used in the experiments with 5 (five) treatment and 3 (three) repetitions. The experimental feed contained 31% of protein and 252.06 Kcal/g of energy. Various doses of the addition of papain enzyme were incorporated into the feed, those doses were A (0 g/kg feed), B (2 g/kg feed), C (4 g/kg feed), D (6 g/kg feed) and E (8 g/kg feed). Parameters of digestibility of protein (ADCP), relative growth rate (RGR), efficiency of feed utilization (EFU), feed conversion ratio (FCR), protein efficiency ratio (PER), survival rate (SR) and water quality were evaluated. The papain enzyme supplement significantly (P<0.01) influenced on ADCp, RGR, EFU, FCR, and PER, otherwise SR of catfish was insignificantly affected by the papain enzyme supplement. The best treatment result was the addition of 6/kg feed papain enzyme (treatment D). The study concluded that the optimum dose of the papain enzyme supplement for ADCp, EFU, FCR, PER and RGR were 5.65, 5.62, 6.0, 5.66, 6.0 g/kg feed respectively. Water quality during study was still in favorable condition for nurturing Sangkuriang catfish (Clarias sp).